DOES GENDER MODERATE THE EFFECT OF EARNINGS MANAGEMENT ON FIRM VALUE? - Anjelina (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
This study aims to examine the effect of earnings management on firm value with gender as moderating variable (the proportion of female directors). Earnings management is measured by real activities (Roychowdhury, 2006), company value is measured by Tobins'Q and there are growth and size as control variables. This paper uses panel data from 545 firm-years non-financial public company listed on the Indonesia Stock Exchange in the period 2011-2015. Data analysis method uses panel data regression analysis with the selection of Random Effect models through STATA software. The results of this analysis reveal, first earnings management has a negative effect on firm value, while the control variables used do not affect the firm value. Second, the proportion of female directors (gender) does not moderate the relationship between earnings management and firm value. This paper provides empirical evidence for management related to investors' response to real earnings management activities and provide an overview to the government, especially tax policy makers in order to anticipate earnings management behavior that has a negative impact on state revenues.